2022
DOI: 10.3389/fonc.2022.824258
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Methyltransferase-Like 14 Promotes Ovarian Cancer Cell Proliferation Through Stabilizing TROAP mRNA

Abstract: Altered expression levels of the proteins that regulate N6-methyladenosine (m6A) RNA methylation, including methyltransferase-like 14 (METTL14), are associated with cancer development. Based on our analysis of m6A methylation regulators using The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets, we focused on the regulatory role of METTL14 in ovarian cancer. We performed bioinformatics and survival analyses with these datasets and also used METTL14-overexpressing SKOV-3 ovarian cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…NAT10 was involved in tubulin processing, associated with cell growth in epithelial ovarian cancer ( 81 ). METTL14 overexpression inhibited cell proliferation of OC through suppressing expression of TROAP based on m6A RNA methylation ( 82 ). IGF2BP3 overexpression inhibited cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…NAT10 was involved in tubulin processing, associated with cell growth in epithelial ovarian cancer ( 81 ). METTL14 overexpression inhibited cell proliferation of OC through suppressing expression of TROAP based on m6A RNA methylation ( 82 ). IGF2BP3 overexpression inhibited cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…METTL14, which inhibits OC cell proliferation, is downregulated in OC tissues (Y. Li, Peng, et al, 2022). Overexpression of METTL14 increases 3 0 UTR m 6 A methylation of troponin-associated protein (TROAP), decreases the stability of its mRNA, and blocks the G1 phase of the OC cell cycle to suppress proliferation (Y.…”
Section: A Writersmentioning
confidence: 99%
“…The studies on OC have shown similar results. Liang et al reported a considerable copy number variation (CNV) in the METTL14 gene in the OC tissues and a decrease in its expression level as well as low m 6 A methylation level [ 40 ]. Further investigation showed that the trophinin-associated protein (TROAP) was a downstream target of METTL14 [ 40 ].…”
Section: A and Ocmentioning
confidence: 99%
“…Liang et al reported a considerable copy number variation (CNV) in the METTL14 gene in the OC tissues and a decrease in its expression level as well as low m 6 A methylation level [ 40 ]. Further investigation showed that the trophinin-associated protein (TROAP) was a downstream target of METTL14 [ 40 ]. METTL14 reduced the mRNA stability of TROAP, inhibiting the proliferation of OC cells at the G1 phase [ 40 ].…”
Section: A and Ocmentioning
confidence: 99%
See 1 more Smart Citation